Variation of ionospheric slab thickness observations at Chumphon equatorial magnetic location - P. Kenpankho; P. Supnithi; T. Tsugawa; T. Maruyama (My University, 2011)
This study presents the diurnal and seasonal variations of slab thickness at the equatorial magnetic latitudes in Thailand during 2004–2006, corresponding to the declining part of low solar activity. The GPS-derived total electron content (TEC) and the maximum electron density of the F-region (NmF2) are used to compute the slab thickness (τ) at the Chumphon station (10.72°N, 99.37°E), located near the magnetic equator. The results show that large peaks of slab thickness exist during the pre-sunrise hours in all three seasons at Chumphon when compared with other latitudes. The maximum value of slab thickness occurs when the peak electron density in the F2 region is at the lowest level. During daytime, the slab thickness ranges from 200 kilometers to 580 kilometers for all seasons. During nighttime, the maximum value of slab thickness is 1250 kilometers in the summer of 2004. Moreover, the diurnal variation shows two minima that appear around 0900 LT and 1900 LT, during the post-sunrise and sunset hours. The seasonal variations show that the average slab thickness daily value is greater during summer and winter than those during equinox. Our study finds that the slab thickness at Chumphon located near the equatorial latitude is much larger than those found at low, mid, and high latitudes. The difference in slab thickness between the equatorial latitude and other zones is explained by the lack of plasma flow from the plasmasphere to the F2 region at the magnetic equator.
Keywords: Slab; Sunrise; Sunset; Plasmasphere; Equinox; Diurnal temperature variation; Magnetic dip; Noon; Solstice; Ionosphere and magnetosphere dynamics